Alcohol, Drug, and Mental Health Specialty Treatment Services and Race/ Ethnicity: A National Study of Children and Families Involved With Child Welfare - Libby, Anne M. (© American Journal of Public Health 2006, 2006)
We used data on a national sample of children involved with child welfare systems to compare American Indian caregivers with White, Black, and Hispanic caregivers in their need for, and receipt of, specialty alcohol, drug, and mental health treatment. American Indian caregivers were significantly less likely to receive services than were Hispanic caregivers (P<.05) but not significantly less likely than were White or Black caregivers. Child placement, child age, and caregiver psychiatric comorbidity were significantly associated with service receipt.